If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 7) = -1(x + -8) Reorder the terms: 2(7 + x) = -1(x + -8) (7 * 2 + x * 2) = -1(x + -8) (14 + 2x) = -1(x + -8) Reorder the terms: 14 + 2x = -1(-8 + x) 14 + 2x = (-8 * -1 + x * -1) 14 + 2x = (8 + -1x) Solving 14 + 2x = 8 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 14 + 2x + x = 8 + -1x + x Combine like terms: 2x + x = 3x 14 + 3x = 8 + -1x + x Combine like terms: -1x + x = 0 14 + 3x = 8 + 0 14 + 3x = 8 Add '-14' to each side of the equation. 14 + -14 + 3x = 8 + -14 Combine like terms: 14 + -14 = 0 0 + 3x = 8 + -14 3x = 8 + -14 Combine like terms: 8 + -14 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 5x+3x=24 | | 9m-7-8=-12(1-m)-2(2m-7) | | 3x+4x=28 | | 3(3)-5y=9 | | t^2+3t=0 | | 3(0)-5y=9 | | -12k-11(-k+11)=-(1+9k) | | 2x+4x=12 | | 3p-2=6p+4 | | -6(x-3)=-9(-2-3x) | | -s^2-13s=0 | | -12-5x=6(8x-2)-4x | | -5(1+8b)=-39-6b | | 3(-1)-5y=9 | | -3(1+8v)=-39-6v | | 4y=-6 | | 7(n-6)=-24+n | | -2y-6=-6y | | -35=5-4x | | 2(f+3)+4f=6+6f | | 4x-8+6x=13+7x | | -2(y-3)=-6y | | 2y+4(1)=8 | | 21-3y=36-6y | | x^3+15x+5=11 | | x^3+15x+5=0 | | 3x+3x=6 | | 2y=3y-20 | | 5*g-5=100 | | 5x+3x=32 | | 4t-1=t+2 | | 5x+y=32 |